One-pot synthesis of 2-thenoyltrifluoroacetone surface functionalised SrF2:Eu3+ nanoparticles: trace level detection of water - Ghosh, Debasish; Luwang, Meitram Niraj (RSC Advances, 2015)
This work reports the one pot synthesis of 2-thenoyltrifluoroacetone (TTA) surface functionalised SrF2:Eu3+ nanoparticles. The nanoparticles were characterised by X-ray diffraction (XRD), infra-red (IR), UV-absorption, transmission electron microscopy (TEM), and photoluminescence studies. Sensitization of Eu3+ ion by TTA in SrF2 nanoparticle matrix gives an enhanced luminescence in dry aprotic solvents like tetrahydrofuran (THF), acetonitrile (AN), dichloromethane (DCM) etc. We studied the effect of trace quantity of water on luminescence of the particles in THF solvent. Even a trace level of water content in the solvent is able to quench the luminescence significantly and quenching enhances with addition of more and more water. This approach of luminescence quenching strategy of detecting a minute trace level of water molecules has a potential application in the estimation of water in various dry organic solvents like THF.